MEDIATION of PROFIT SHARING TO DEVELOP MSMEs WITH MUDHARABAH CAPITALIZATION SCHEMES - Afkar, Taudlikhul; Miradji, Moch. Afrizal; Fauziyah, Fauziyah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to show the development model of MSMEs with mudharabah capital schemes through the principle of profit sharing distribution from the perception of MSME actors. The object of research is in East Java by using a sample of three regions using random with total of 75 respondents who were obtained incidentally considering the number of MSMEs is very much. The analysis technique used is multivariate analysis using Warp PLS. The results showed that mudharabah financing with mudharabah mutlaqah, mudharabah muqayyadah and mudharabah mustyarakah financing schemes significantly influence the principle of profit sharing distribution. Furthermore, the mudharabah mutlaqah, mudharabah muqayyadah, mudharabah mustyarakah, and profit sharing distribution principles have a significant effect on the development of MSMEs. The profit sharing distribution principles can be mediated in the development of MSMEs with a capital scheme mudharabah mutlaqah, mudharabah muqayyadah, mudharabah mustyarakah. The recommended MSMEs Development Model is the Mudharabah capital scheme through the mediation of fairly in principles of profit sharing distribution.